1999
DOI: 10.2307/2586112
|View full text |Cite
|
Sign up to set email alerts
|

Democracy and Social Spending in Latin America, 1980–92

Abstract: What is the effect of regime type on public expenditures for social programs? We investigate the relationship between democracy and the change in social spending—controlling for GDP, the debt, inflation, and age structure of the population—through a time-series cross-sectional panel data set for 17 Latin American countries from 1980 to 1992. The results show that, especially in poor countries during economic crisis, democracies increase the allocation of resources to social programs relative to authoritarian r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(177 citation statements)
references
References 26 publications
(22 reference statements)
7
158
0
3
Order By: Relevance
“…This paper contributes to a small but growing literature that examines whether democracies behave differently from their authoritarian counterparts when it comes to the provision of public services. Work by Brown and Hunter (1999), Kaufman and Segura-Ubiergo (2001), and Ames (1987) has found that democracies in Latin America tend to spend more on items like education and health than do autocracies. Brown and Hunter (2004) have found that Latin American democracies have spent more on primary education in particular.…”
mentioning
confidence: 99%
“…This paper contributes to a small but growing literature that examines whether democracies behave differently from their authoritarian counterparts when it comes to the provision of public services. Work by Brown and Hunter (1999), Kaufman and Segura-Ubiergo (2001), and Ames (1987) has found that democracies in Latin America tend to spend more on items like education and health than do autocracies. Brown and Hunter (2004) have found that Latin American democracies have spent more on primary education in particular.…”
mentioning
confidence: 99%
“…The interpretation of this result is somewhat difficult, but this may reflect the chaos in general governmental functions in the midst of a regime transition, given that the expenditure on general public services includes expenses for financial and fiscal affairs and diplomacy. 16 15 An increase in total expenditure in countries classified under the category "reversals" may especially reflect the events in Zimbabwe. Zimbabwe witnessed a reversal in 1987.…”
Section: Discussionmentioning
confidence: 99%
“…Because our sample includes only two countries that have undergone reversal, Gambia and Zimbabwe, it is difficult to judge whether the results reflect the political events in these two countries over a period or if they are generalized (i.e., apply to all reversals). 15 The same caveat also applies to the results for borderline democratization because only six countries are classified as such in our sample.…”
Section: Different Types Of Transitionsmentioning
confidence: 93%
“…Bu araştırmalarda elde edilen ortak sonuç ise demokratik bir rejime sahip olan ülkelerde anti-demokratik ülkelere göre daha fazla sosyal hizmetlere yönelik harcama yapılmak-ta olduğudur (Kaufman ve Segura, 2001;Brown ve Hunter, 1999;Ross, 2011;Stasavage, 2005;Huber, Mostrilo ve Stephens, 2008). Nitekim Huber, Mostrillo ve Stephans (2008), sosyal harcamaların temel belirleyicilerini ve sınırlılıklarını inceledikleri çalış-malarında, demokratik bir yönetime sahip ülkelerin uzun dönemde sosyal güvenlik, sağlık ve eğitim alanlarına eşanlı olarak daha fazla kaynak ayırdıkları sonucuna ulaşmışlardır.…”
Section: Literatür İncelemesiunclassified